Instruction and improvisation under neoliberalism. Issue 1 (2nd January 2019) - Gershon, Ilana; LaDousa, Chaise
ABSTRACT: Bonnie Urciuoli has become a pioneer for her work on neoliberal discourses in higher education. We introduce this work as well as the articles gathered herein to honour it. The articles engage with Urciuoli's work by considering neoliberal discourse in various institutional contexts. Important in all of the articles is a critique of the control neoliberalism would seem to offer.